Effects of leaf age during drought and recovery on photosynthesis, mesophyll conductance and leaf anatomy in wheat leaves - Jahan, Eisrat; Sharwood, Robert Edward; Tissue, David T. (Frontiers in Plant Science, 2023)
Summary statement: Mesophyll conductance (gm) was negatively correlated with wheat leaf age but was positively correlated with the surface area of chloroplasts exposed to intercellular airspaces (Sc). The rate of decline in photosynthetic rate and gm as leaves aged was slower for water-stressed than well-watered plants. Upon rewatering, the degree of recovery from water-stress depended on the age of the leaves, with the strongest recovery for mature leaves, rather than young or old leaves. Diffusion of CO2 from the intercellular airspaces to the site of Rubisco within C3 plant chloroplasts (gm) governs photosynthetic CO2 assimilation (A). However, variation in gm in response to environmental stress during leaf development remains poorly understood. Age-dependent changes in leaf ultrastructure and potential impacts on gm, A, and stomatal conductance to CO2 (gsc) were investigated for wheat (Triticum aestivum L.) in well-watered and water-stressed plants, and after recovery by re-watering of droughted plants. Significant reductions in A and gm were found as leaves aged. The oldest plants (15 days and 22 days) in water-stressed conditions showed higher A and gm compared to irrigated plants. The rate of decline in A and gm as leaves aged was slower for water-stressed compared to well-watered plants. When droughted plants were rewatered, the degree of recovery depended on the age of the leaves, but only for gm. The surface area of chloroplasts exposed to intercellular airspaces (Sc) and the size of individual chloroplasts declined as leaves aged, resulting in a positive correlation between gm and Sc. Leaf age significantly affected cell wall thickness (tcw), which was higher in old leaves compared to mature/young leaves. Greater knowledge of leaf anatomical traits associated with gm partially explained changes in physiology with leaf age and plant water status, which in turn should create more possibilities for improving photosynthesis using breeding/biotechnological strategies.